Insights from primary immunodeficiencies: investigating the role of GIMAP6 in the immune system - Chao, B (2018)
While molecular, cellular, and animal models play a vital role in immunological research, the study of patients with inborn errors of immunity provides a unique opportunity to elucidate the direct importance of specific genes in the human immune system. In this thesis, I have investigated the disease etiology of four sets of patients believed to have novel primary immunodeficiencies (PIDs) using whole exome sequencing coupled with in vitro and in vivo assays of both patient cells and model systems. In one patient, I confirmed a mutation in DNMT3B, a DNA methyltransferase known to cause a previously identified PID. I next investigated whether a homozygous missense mutation in TICAM2, a toll-like receptor signaling adaptor, might underlie the disease of a patient with recurrent pneumonia. In collaborative project, I then examined the potential role of a newly described PID-associated gene, GTPase of the immunity-associated protein 5 (GIMAP5), in autophagy and metabolism. GIMAP5 is a member of a family of conserved GTPases with a poorly understood role in leukocyte development and survival. Stemming from the work on the GIMAP5 cohort, I identified a patient presenting with splenomegaly and autoimmunity who has a novel homozygous missense mutation in GIMAP6. The majority of this thesis focuses on verification of GIMAP6 as a PID-associated gene and investigation of its molecular function. Using both patient cells and knockout mouse models, I demonstrated an autophagic defect in GIMAP6-deficient T cells, implicating GIMAP6 as a regulator of autophagy. Furthermore, I determined that Gimap6 knockout mice have early mortality due to microangiopathic kidney disease. I demonstrated that this renal disease was not immune-mediated therefore implying that GIMAP6 has a novel role in endothelial cell function. The work presented in this thesis thus highlights both the challenges of studying PIDs and the promise of these diseases to help elucidate the mechanisms of human immunity and therapies for PID patients.